International Accounting Standards for Line‐of‐Business Reporting and Oligopoly Competition* - GIGLER, FRANK; HUGHES, JOHN; RAYBURN, JUDY (Contemporary Accounting Research, 1994)
Abstract. This article presents a model in which the impact of international accounting standards on product market competition can be assessed. Formulating the choice of disclosure rules as the first stage in a multistage game between countries and representative incumbent and entrant firms, we establish conditions under which an enforceable international standard to require line‐of‐business (LOB) reporting could lead to strict improvement in the expected national welfare of participating countries over the equilibrium that would otherwise be attained. Additional results consider the effects of changes in certain model assumptions and the addition of tariffs as further trade policy instruments. Résumé. Les auteurs proposent un modèle permettant d'évaluer l'incidence des normes comptables internationales sur la concurrence, sur les marchés de produits. Ils posent d'abord le choix des règles de présentation de l'information comme étant la première étape d'un jeu à multiples épisodes entre les pays et entre les sociétés en place représentatives du secteur et les nouvelles venues. Ils établissent ensuite les conditions dans lesquelles l'application possible d'une norme internationale exigeant la publication d'information sectorielle pourrait mener à une stricte amélioration de la prospérité nationale attendue des pays participants, au‐delà du niveau d'équilibre qui serait autrement atteint. Les auteurs s'intéressent entre autres, dans leurs travaux, aux répercussions de la modification de certaines hypothèses du modèle et de l'introduction des tarifs douaniers à titre d'instruments de la politique d'échange.